PERANAN KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN DALAM PENANGANAN KASUS PIDANA LINGKUNGAN HIDUP DAN KEHUTANAN - Ramadhan, Muhammad Syahri (Indonesian Journal Of Law Studies, 2024)
This research examines the role of the Ministry of Environment and Forestry (KLHK) in handling environmental and forestry criminal cases in Indonesia. The aim is to analyze the effectiveness of the KLHK's role as a government institution responsible for enforcing environmental and forestry laws. The research method used is a normative approach. The research results show that the Ministry of Environment and Forestry has a strategic role in handling environmental and forestry criminal cases, starting from prevention, supervision, to law enforcement. However, there are still several obstacles in its implementation, such as limited human resources, budget and coordination between institutions. This research recommends strengthening the capacity of the Ministry of Environment and Forestry and increasing synergy with other law enforcement institutions to optimize the handling of environmental and forestry criminal cases in Indonesia.